ASSESSING THE FINANCIAL DISTRESS RISK OF LISTED NON-FINANCE FIRMS IN NIGERIA: THE CEO DIMENSION - Ibida, Nneka J.; Onuora, Joshua K.J.; Ofor, Nkechi Theresa (Journal of Global Accounting, 2023)
The study assesses financial distress in the context of CEO attributes by employing samples from listed non-finance firms in Nigeria between the periods of 2012-2021. CEO turnover and CEO Gender are the CEO characteristics employed in this study as the explanatory variables while financial distress risk measured in terms of Altman Z-score Model and the Zmijewski’s Model are the dependent variables. Longitudinal research design was employed since the study sought to examine the effect of CEO characteristics on firm financial distress risk of 70 listed non-financial firms in Nigeria from 2012 – 2021. The data were sourced from related companies’ annual financial reports for the periods as well as the Nigerian Exchange Limited Websites (secondary data). Overall, mixed empirical findings were obtained while assessing the effect of CEO characteristics on financial distress risk of listed non-finance firms in Nigeria. The study concluded that CEO gender has a significant positive effect on financial distress risk when proxied in terms of Altman Z-score of listed firms in Nigeria. The study further documents that CEO gender has a significant positive effect on financial distress risk when proxied in terms of Zmijewski score of listed firms in Nigeria during the period under study. As for CEO turnover, study concluded that it has an insignificant positive effect on financial distress risk when proxied in terms of Altman Z-score and Zmijewski score of listed firms in Nigeria during the period under study. Since female CEOs have lower leverage, less volatile earnings, and a higher chance of survival than firms with male CEOs, this study therefore advocates the promulgation of policies that will encourage women act as CEOs’ which will go a long way to extend firms’ life spans.